Innovation in a reinvented world 10 essential elements to succeed in the new world of business - McCrorey, Dee, 1953- (Wiley, 2012)
"A step-by-step guide to the 10 essential and practical skills a business needs to innovate and thrive in uncertain timesThe reinvented world of business will profoundly impact America's leaders and workers in the decade ahead. Companies capable of transforming their organizations during this period of "Great Disruption" will thrive in the reinvented world however, the reverse holds true as well. Innovation in a Reinvented World reveals how transformation occurs when business leaders and their organizations apply these 10 Essential Elements, providing both a road map and definitive blueprint for companies of any size looking to bridge the old world with the new world of business. Discusses the "new courage" required for innovating in a reinvented world Looks at 10 Essential Elements winning companies count on today Innovation in a Reinvented World helps executives and leadership teams navigate and manage their organizations' inflection points in designing, building, and sustaining innovation--even through the post-recession playing field"--